2015
DOI: 10.1093/icvts/ivv025
|View full text |Cite
|
Sign up to set email alerts
|

‘Early’ and ‘late’ timing for renal replacement therapy in acute kidney injury after cardiac surgery: a prospective, interventional, controlled, single-centre trial

Abstract: This trial is registered in the clinicaltrial.gov registry: NCT01961999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Fifteen trials [1720, 2333] with a total of 1479 patients (771 patients receiving early RRT versus 708 patients receiving late RRT) ultimately met our criteria (Table 1); these included five RCTs [17, 18, 23, 25, 33], one prospective cohort study [29] and nine retrospective cohort studies [19, 20, 24, 2628, 3032]. The characteristics and methodological quality of all the included studies are shown in Table 1 and the outcomes in patients with AKI after cardiac surgery are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen trials [1720, 2333] with a total of 1479 patients (771 patients receiving early RRT versus 708 patients receiving late RRT) ultimately met our criteria (Table 1); these included five RCTs [17, 18, 23, 25, 33], one prospective cohort study [29] and nine retrospective cohort studies [19, 20, 24, 2628, 3032]. The characteristics and methodological quality of all the included studies are shown in Table 1 and the outcomes in patients with AKI after cardiac surgery are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Some other studies showed the association between increased prevalance of arrythmias of patients with ARF and acute coronary syndromes [24]. In our study, despite atrial fi brillation, ventricular fi brillation, ventricular tachycardia and cardioversion rates were similar in both groups but signifi cant hours follow-up of urine output less than 0.5 mL/kg/hour [26].…”
Section: Post Operative Outcomessupporting
confidence: 60%
“…An argument has been made by Ronco et al [17] that this study, along with other recent observational studies [21,23] supports a conclusion that, while early initiation may or may not be beneficial, avoiding or delaying it is associated with increased mortality. We do not agree that this has been clearly established given that recent studies do not consistently report either that delaying or avoiding RRT is harmful, or that earlier initiation is harmless [30][31][32][33][34][35][36] . In particular, multiple, observational studies published in the last 5 years suggest that delaying or avoiding RRT may be beneficial [31,32,34,35] .…”
Section: Insufficient Evidence To Support Ever Earlier Rrtmentioning
confidence: 87%
“…While consensus has been established that RRT should be initiated for 'conventional', potentially lifethreatening indications, the threshold for starting has been lowered such that many patients begin RRT preemptively. Despite this change in practice, there was insufficient evidence to support it: multiple observational studies have suggested decreased mortality with 'earlier' RRT [11,[21][22][23], but many others have suggested that there is no effect [33,36] or that a conservative strategy is superior [30,32,34,35] . In addition, 3 underpowered RCTs have been conducted and none of them have shown significantly improved outcomes with relatively earlier RRT initiation [20,37,38] .…”
Section: Discussionmentioning
confidence: 99%